Representasi Komunikasi Lingkungan pada Revitalisasi Sungai - Salsabilla Putri Mulyana; Alex Sobur (Bandung Conference Series: Public Relations, 2023)
Abstract. Issues regarding the environment become a conversation that dominates every day because the increase is significant. The issue of river pollution is much discussed, considering that the river is a source of water that is widely used by the community. One of the heavily polluted rivers is the Citarum river, which has been named the dirtiest river by the World Bank. The government is trying to revitalize the Citarum river by holding the Citarum Harum program. Environmental communication on the revitalization of the Citarum river which involves many people with different backgrounds. Representations regarding environmental communication carried out in the revitalization of the Citarum River are research questions that will be examined in this study. This study uses a qualitative paradigm with ethnographic methods. The selected data collection techniques are in-depth interviews, observation and documentation. Data triangulation was chosen as a way to test the validity of the data through methods, investigators and theory. Reviewed using representation theory, environmental communication theory. The results of this study are that the form of a reflective approach to environmental communication regarding the revitalization of the Citarum River is in the form of socialization, education and invitation activities for the community carried out by the Citarum Task Force. In the intentional approach after environmental communication, it has an impact on both communicators and communicants, including increasing awareness about the importance of rivers and protecting the environment more. The form of the constructivist approach carried out by the Citarum Task Force is the making of an appeal sign. Keywords: Citarum River, Environmental Communication, Representation Theory, Citarum Harum Program Abstrak. Isu mengenai lingkungan menjadi perbincangan yang mendominasi setiap hari karena peningkatannya signifikan. Isu mengenai pencemaran sungai menjadi hal yang banyak diperbincangkan, mengingat sungai merupakan sumber air yang banyak dimanfaatkan oleh masyarakat. Salah satu sungai yang tercemar berat adalah sungai Citarum yang dinobatkan sebagai sungai terkotor oleh Bank Dunia. Pemerintah berusaha untuk melakukan revitalisasi sungai Citarum dengan mengadakan program Citarum Harum. Komunikasi lingkungan pada revitalisasi sungai Citarum yang melibatkan banyak kalangan yang memiliki latar belakang berbeda. Representasi mengenai komunikasi lingkungan yang dilakukan pada revitalisasi sungai citarum menjadi pertanyaan- pertanyaan penelitian yang akan di teliti dalam penelitian ini. Penelitian ini menggunakan paradigma Kualitatif dengan metode Etnografi. Teknik pengumpulan data yang dipilih adalah wawancara mendalam, observasi serta dokumentasi. Triangulasi data dipilih sebagai cara untuk menguji keabsahan data melalui metode, penyidik serta teori. Dikaji menggunakan teori representasi, teori komunikasi lingkungan. Hasil dari penelitian ini bahwa bentuk pendekatan reflektif pada komunikasi lingkungan mengenai revitalisasi Sungai Citarum berupa kegiatan sosialisasi, edukasi dan ajakan untuk masyarakat yang dilakukan oleh Satgas Citarum. Pada pendekatan intensional pasca komunikasi lingkungan memberikan dampak baik bagi komunikator maupun komunikan diantaranya dapat meningkatkan kesadaran mengenai pentingnya sungai dan lebih menjaga lingkungan. Bentuk pada pendekatan konstruktivis yang dilakukan Satgas Citarum adalah pembuatan plang himbauan. Kata kunci : Sungai Citarum, Komunikasi Lingkungan, Teori Representasi, Program Citarum Harum